The Form of Tapah Malenggang Folklore from Batanghari Regency, Jambi Province - Irma Suryani; Dwi Rahariyoso; Nurfitri Susanti (Proceeding International Conference on Malay Identity, 2020)
This research describes the form of the Tapah Malenggang folklore based on the transcription conducted by Datuk Rasyid from the utterances of Datuk Zainul and Datuk Saharman. The folklore of Tapah Malenggang, as part of the oral literature of the Batanghari people, is gradually shrinking, and it can even be said to be on the verge of extinction. Through this research, it is hoped that the folklore of Tapah Malenggang can be found. The method used is descriptive analysis. The results showed that the Tapah Malenggang folklore was in the form of myths which functioned structurally to formulate the folk tales as myths. Key words: Form of folklore, myth, Tapah Malenggang